Coping, Personal and Family Life of Professors who belong to the National System of Researchers of a University of the South of México - Ramón Santiago, Pedro (2020)
This study aimed to know the self-perception of the dimensions of coping, as well as personal and family life of researchers belonging to the National System of Researchers (SNI) of a public university in southeastern, Mexico. It was developed from a quantitative, descriptive-exploratory perspective. The study was made up of 121 (96%) of the researchers assigned to the SNI, of which 72 (59.5%) are men (M age = 43.3, SD = 9.5 years) and 49 (40.5%) women (M age = 44.2, DE = 8.4 years). The information-gathering instrument was a questionnaire that was answered with a Likert scale, as well as three open questions. It was found that the members of the SNI of the University of the study are young, and have mostly recognition at level I. In relation to the dimensions of coping and personal and family life, the subjects are almost always satisfied with the variables associated with these dimensions. In sum, the factors that influence their permanence or admission to the SNI, are the skills they possess, the interest, the family and the preparation they received in the field of research.